Exploration of Academic Experiences and Challenges Faced by Visually Impaired Student at University - Zainab Kamran; Rashid Maqbool; Saira Zafar (Journal of Information Management and Practices)
The notion of inclusion in education undertakes the principle that each student has a right to equitable access to education. It also expects that all educational institutions must organize learning spaces that facilitate every student either gifted, special or general. It is an on-going process and quest, aimed to increase participation of all learners in learning process. In this study the author was focused to get an insight regarding academic challenges and experiences through the lens of visually impaired student in an inclusive classroom at university. Case study approach was used to get the insight about learning experiences and challenges of visually impaired student. To select the single case for the study purposive sampling was used. Semi-structured interview guide was developed to collect the data. The collected data was transcribed and after that thematic analysis was used to develop themes from the data. Major themes emerged as a result of thematic analysis are Life changing event, Role of a teacher, Challenges regarding admission, classroom activities and peers behaviour and lastly Measures to support gifted student in an inclusive classroom. The study findings revealed that problems and challenges experienced by visually impaired student are associated with teachers who are unskilled and non-proficient in the execution of their duties in an inclusive classroom as well as the negative attitude and unsupportive behaviour of peers towards them. These findings will be helpful for departments and university on how they can take effective measures to address these problems and improve learning environment to make such students feel supported and a part of general classroom.